(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Teacher stress is inevitable in the education industry. Stressors causing stress are dynamic in nature. Thesestressors could be visible or invisible. Visible stressors are directly job-related whereas invisible stressors are known as camouflagedstress that are specificallyrelatedtotheteacher.Work-relatedstressorshavebeenexhaustivelylistedin ample previous research works but the impact of VUCA (Volatility, Uncertainty, Complexity and Ambiguity)worldneedsanemphasisonthestudyofteacherstress.Dealingwithteacherstressisalthoughachallengebutisquintessential for well-being of an academician. Earlier studies suggested stress coping strategies that need extra timeand sources like, exercise, nutritional diets, sleep patterns, meditation, yoga, time management and alike. Thispaperaimstostudythemindsetasastress-copingstrategy.Therootcauseofstressismindthusitshouldbedealt at the mental level. The human mind can be classified into two viz., rational mind and emotional mind. Theintensityofemotionsdecidesthelevelofdominationbytheemotionalmindovertherationalmind.Strikingtheright balance between the two minds paves way for coping stress. The paper concludes that stressors causingstress should be understood, acknowledged and dealt appropriately.